Interaction Of Mgo-Mgr2o4(R: Al, Cr, Fe) Refractories With SO2-Containing Gases - N. Z. Fotoyi (The Southern African Institute of Mining and Metallurgy, 2011)
Keywords: MgO-MgR2O3 refractory, SO2-containing gases, chemical attack The reaction mechanisms occurring when MgO-MgR2O3 refractories are exposed to SO2-containing gas atmospheres were examined. The study examined the characteristic structures of magnesite-chrome, chrome-magnesite and magnesite refractories exposed to SO2-O2 gas mixture at temperatures of 700°C to 1350°C. The phase characterization was conducted with scanning electron microscopy (SEM) and powder X-ray diffractometry (XRD). The results show that the physical characteristics of the refractory matrix along the grain boundaries are important refractory features during chemical attack from SO2-containing gas. Upon heating in SO2-containing gas, the changes in phase-chemical compositions and accompanying grain growth causes loosening of the structure and the pore volume promotes gas diffusion. The chemical reactions that occur form stable sulfate compounds identified as MgSO4, CaSO4 and CaMg3(SO4)4, and lead to disintegration of various phase structures and consequently erosion of the refractory. In conclusion, the reaction mechanisms in MgO-MgR2O3 refractories exposed to SO2-containing gases progress through a combination of structural disintegration and chemical attack.